Paracooperia nodulosa in a local domestic goat - Lee, C. C.; Babjee, Shaik Mohamed Amin; Sheikh Omar, Abdul Rahman; Mohna, S. S. (Veterinary Association Malaysia, 1989)
A male Paracooperia nodulosa was recovered from the small intestine of a slaughtered four-year-old female goat from Perak, Malaysia. Its morphology and measurements are provided. This constitutes a new record of P. nodulosa in the domestic goat